The Sand Warrior - Mark Siegel (Random House, 2017)
The Five Worlds are on the brink of extinction unless five ancient and mysterious beacons are lit. When war erupts, three unlikely heroes will discover there$1 (Bs more to themselves$1 (Band more to their worlds$1 (Bthan meets the eye. . . . Oona Lee, the clumsiest student at the Sand Dancer Academy, is a fighter with a destiny bigger than she could ever imagine. An Tzu, a boy from the poorest slums, has a surprising gift and a knack for getting out of sticky situations. Jax Amboy is the star athlete who is beloved by an entire galaxy, but what good is that when he has no real friends? When these three kids are forced to team up on an epic quest, it will take not one, not two, but 5 WORLDS to contain all the magic and adventure!s
Keywords: Mystery -- Mystery